Prevalence of normal occlusal traits in deciduous dentition (Pesquisa Odontológica Brasileira, 2001)
The aim of this research was to study the normal occlusal patterns of deciduous dentition in Brazilian preschool children. The sample consisted of 356 preschool children, of both genders, aged 3-5 ½ years from the urban zone of Salvador, Bahia. The occlusion exam was carried out by two examiners, in the classroom, utilizing a wooden spatula. The data were analyzed by the statistical program EPI-INFO 6.02 using the Chi-squared test. The frequency of the type I arch was 43.3% for the upper and 46.3% for the lower arch. The frequency of the type II arch was 56.7% for the upper and 53.75 for the lower arch, however, no difference between genders was noticed. The distribution of primate spaces was: 89.9% for the upper and 67.1% for the lower arch. This prevalence decreased significantly as age increased (p < 0.01). Normal canine relationship was found in almost 60% of the children for the right and left sides. Out of 712 evaluated terminal planes, 55.9% presented mesial terminal step for the primary second molars, 37.9% straight terminal plane and 6.2% distal step. The results permitted to conclude that the presence of generalized spacing between incisors, commonly described by other authors, was not the most prevailing condition for both arches in this sample. On the other hand, primate spaces were the most common ones. The most frequent normal occlusal patterns for canine and molar relationships were found to be the Class I patterns.